Indonesia : Indonesia - Widiastuti, Maria Rina; Subiyanto, Paulus; Ratnawati, Emilia (STIKes Panti Rapih, 2023)
Backgroud: Covid-19 disease is a disease that attacks the respiratory tract with mild symptoms, without symptoms, until severe acute respiratory syndrome occurs. Covid-19 transmission occurs through droplets in the form of patient saliva, mucus and sputum. The Covid-19 pandemic is causing mental health problems in both people who are infected, not infected or not known to be infected. The results of the preliminary study found that 9 employees at Panti Rahayu Hospital with positive confirmation of Covid-19 experienced variations in length of stay, stress levels, and coping mechanisms. Aim:This study aims to obtain an overview of the stress level and coping mechanisms of employees for confirmation of Covid-19. Method: The research method used is mix methods by combining quantitative and qualitative descriptive research. The study population was all employees of Covid-19 confirmation with a total sampling of 15 respondents. Collecting data using a survey method, by questionnaire and structured interviews. The stress level was measured by using the Depression Anxiety Stress Scale (DASS) questionnaire and the coping mechanism was measured by the ways of coping quesionare (revised). Result: The results showed that the number of employees confirming Covid -19 with mild stress levels was 6 respondents (40%), moderate stress was 2 respondents (13%) and severe stress was 7 people (47%). The adaptive coping mechanism used was 11 respondents (73%) and 4 respondents in a maladaptive way (37%). With the chi-square test, there is a significant relationship between stress levels and the coping mechanism of Covid-19 confirmation employees with a p value of 0.044 (α: 0.05). Conclusions: The lower the stress level, the coping mechanism used tends to be adaptive, while those who experience severe stress levels tend to use the maladaptive coping mechanism. Keywords: stress level, coping mechanism, Covid-19